Help-Seeking Preferences and Factors Associated with Attitudes Toward Seeking Mental Health Services Among First-Year Undergraduates - Samuel, Rosalia; Kamenetsky, Stuart B. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
Many first-year university students experience stressors that impact their adjustment and well-being. Their help-seeking attitudes and preferred sources of support may be associated with various factors. The purpose of the present study was to (1) examine help-seeking preferences amongst first-year university students, (2) explore factors associated with students’ attitudes toward seeking mental health services, and (3) identify perceived barriers associated with accessing formal sources of support. First-year students at a Canadian university (N = 167) completed a survey assessing help-seeking attitudes and preferences, as well as challenges associated with seeking support. Participants also provided information about their perceived levels of social support, personality characteristics, and their tendency to experience positive and negative affect. Findings suggest that social support and negative affect were significantly associated with positive attitudes toward seeking mental health services. However, students were more inclined to rely on informal sources of support, such as family members and friends, compared to formal sources of support available through on- or off-campus mental health services. For thosestudents who are inclined to access formal mental health support, barriers may impede access to care. Perceived barriers include cost and concerns about the availability of services and their overall effectiveness. These findings call for the creation of more opportunities for on-campus informal support in addition to better access to on-campus mental health services.